Family values and female psychological aggression - Edalati, Ali; Redzuan, Ma’rof; Mansor, Mariani; Abu Talib, Mansor (Science Publications, 2010)

(untitled)
The main objective of the current study is to determine the relationship between women’s perceptions toward Iranian family values with psychological aggression. Approach: All of the randomly selected 337 wives who suffered from level of psychological aggression were included in this study. Straus questionnaire (CTS) is the method used to measure psychological aggression. It shows a negative relationship between family values (inequality in affairs and inequality in regulation) and psychological aggression. It has also shown that there is no relationship between values of inequality in access job and inequality in political in relation to psychological aggression. Social learning theory is used in order to gain a thorough understanding of the issue. The multivariate regression analysis is utilized to answer the last objective. Results: The analysis showed that among the four predictor variables, two of which variables such as inequality in affairs and inequality in regulation were found to be significant in explaining the observed variation in psychological aggression (DV). Conclusion: Generally, the final model has explained 4% of total observed variance in psychological aggression.